Differential Taxation and Occupational Choice - Renato Gomes; Jean-Marie Lozachmeur; Alessandro Pavan (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study nonlinear income taxation in a Roy model in which agents' productivity is sectorspecific. We show that when income taxes can be sector-specific, the Diamond-Mirrlees theorem (according to which the second-best displays production efficiency) fails: social welfare (be it Rawlsian or Weighed Utilitarian) can be increased by assigning some agents to their least productive sector. By sacrificing production efficiency, the planner incurs second-order losses in total output, but obtains a first-order reduction in the informational costs of redistribution. The same result obtains when the government is constrained to a uniform income tax schedule, as long as sales taxes can be made sector-specific. In this latter case, our result also implies failure of the Atkinson-Stiglitz theorem (according to which, when preferences over consumption and leisure are separable, as they are in our economy, the second-best can be implemented with zero sales taxes).
Keywords: C72; D62; 330; income taxation; occupational choice; sales taxes; sector-specific taxation; production efficiency